Parallel Implicit Runge-Kutta Methods for Stiff ODEs - Bashir M. S. Khalaf; Abdulhabib A. A. Murshid (AL-Rafidain journal of computer sciences and mathematics, 2004)
The main objective of this paper is to develop and construct numerical algorithms for solving stiff system of ordinary differential equations (ODEs) which are suitable for running on parallel computers (MIMD computers).Semi-parallel implicit Runge-Kutta methods have been derived and parallel predictor - corrector methods are developed.